2022
DOI: 10.2147/ijgm.s353762
|View full text |Cite
|
Sign up to set email alerts
|

A Pyroptosis-Related Gene Signature Associated with Prognosis and Tumor Immune Microenvironment in Gliomas

Abstract: Background Pyroptosis is a novel form of cell death that plays a significant role in cancer, while the prognostic values of pyroptosis-related genes in gliomas have not been revealed. Methods We analyzed the RNA-seq and clinical data of gliomas from the University of California Santa Cruz (UCSC) Xena database to determine differentially expressed pyroptosis-related genes. Based on these genes, a pyroptosis genes signature was constructed after univariate Cox analysis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…Immune checkpoint inhibitors(ICIs) known as an important immunotherapy option have showed promising therapeutic effects in various solid tumors including melanoma, bladder as well as renal cancer [ 73 ].However, this novel therapeutic approach failed to elicit response in most of PAAD patients, and tumor genotyping system that identify patients more likely to benefit from ICIs treatment was limited. Our research revealed that patients in low-risk group exhibited higher expression of ICIs-related moleculars such as PD-1, CTLA-4, TIM-3 and CXCR4, and it has been reported that the expression level of ICIs-related moleculars can serve as a biomarker to forecast the efficacy of ICIs therapy [ 23 ]. PD-1 is expressed on a variety of immune cells especially on activated T cells, and also marked as an indicator for activation of CD8 + T-cell [ 74 ], which consistent with the finding that higher expression of PD-1 indicated better prognosis.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Immune checkpoint inhibitors(ICIs) known as an important immunotherapy option have showed promising therapeutic effects in various solid tumors including melanoma, bladder as well as renal cancer [ 73 ].However, this novel therapeutic approach failed to elicit response in most of PAAD patients, and tumor genotyping system that identify patients more likely to benefit from ICIs treatment was limited. Our research revealed that patients in low-risk group exhibited higher expression of ICIs-related moleculars such as PD-1, CTLA-4, TIM-3 and CXCR4, and it has been reported that the expression level of ICIs-related moleculars can serve as a biomarker to forecast the efficacy of ICIs therapy [ 23 ]. PD-1 is expressed on a variety of immune cells especially on activated T cells, and also marked as an indicator for activation of CD8 + T-cell [ 74 ], which consistent with the finding that higher expression of PD-1 indicated better prognosis.…”
Section: Discussionmentioning
confidence: 92%
“…On the contrary, the proinflammatory cell death induced by pyroptosis could accelerate immune evasion and facilitate a suitable tumor microenvironment for tumor growth [ 20 ]. To date, the survival predicting ability of pyroptosis-related signature has been extensively studied in multiple tumor types including lung adenocarcinoma(LUAD) [ 21 ], hepatocellular cancer [ 22 ] and gliomas [ 23 ].Unfortunately, the clinical prognostic significance of pyroptosis in PAAD is still unclarified.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, periodontitis (a type of chronic inflammation) promotes breast cancer metastasis in the early stages through pyroptosis ( 123 ), Zunjie Zhou et al. discovered that pyroptosis may promote glioblastoma development by inducing chronic inflammatory microenvironments ( 124 ), indirectly proving the role of ROS-induced chronic inflammation in promoting tumors through pyroptosis.…”
Section: Ros Regulates Pyroptosis In Cancermentioning
confidence: 99%